Comparison the effects of ginger (Zingiber officinale) jelly and piroxicam jelly on pain of knee osteoarthritis - Morteza Dehghan; Abbas Abdoli-tafti; Foroozan Ganji; Rasoul Ghaedi (مجله علمی دانشگاه علوم پزشکی کردستان, 2018)
Background and Aim: Oral drugs and nonsteroidal anti-inflammatory drugs which are used to relieve pain are associated with certain side effects in the patients with knee osteoarthritis. The aim of this study was to compare the effects of a herbal drug, Zingiber officinale jelly, and piroxicam jelly on pain relief, morning stiffness, and physical performance in the patients with knee osteoarthritis. Material and Methods: In this semi-experimental study one hundred and twenty patients with osteoarthritis were randomly assigned to three groups of 40. Z. officinale 2% jelly, piroxicam jelly, and placebo were given twice a day for 14 days to the 1st, 2nd and 3rd groups respectively. Concurrently, diclofenac tablet 100mg/ day was given to all groups. Physical examination was performed before intervention and two weeks after completion of the treatment. The level of pain was measured by use of visual analogue scale. Furthermore, the WOMAC index was used to investigate the effect of pain on the patientschr('39') performance. Using SPSS software, data were analyzed by paired t-test, chi-square and ANOVA. Result: There were no significant difference between Z. officinale jelly and piroxicam jelly in relation to relief of overall pain and morning stiffness, (P>0.05). The relief of pain (P=0.01) and morning stiffness (P=0.002) were significantly more marked in the piroxicam-treated group compared to those in the placebo group. Improvement of the physical functioning was not significantly different between the piroxicam-treated and Z. officinale-treated groups (P>0.05). Conclusion: Z. officinale jelly and piroxicam jelly were effective in pain relief, amelioration of morning stiffness, and improvement of physical functioning in the patients with knee osteoarthritis, and there were no significant differences between the effects of the jellies. Key words: Osteoarthritis, Ginger jelly, Piroxicam jelly.